2003
DOI: 10.1002/jcb.10508
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D enhances mitogenesis mediated by keratinocyte growth factor receptor in keratinocytes

Abstract: The hormonally active vitamin D metabolite, 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)), and keratinocyte growth factor (KGF) belong to the network of autocrine and paracrine mediators in the skin. Both were shown to modulate keratinocyte proliferation, to reverse epidermal atrophy, to increase wound healing, and to reduce chemotherapy-induced alopecia. The overlap between their activities may suggest that vitamin D exerts some of its actions by modulation of KGF activities in the skin. This notion was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Erk1/2 Activation and Mitogenic Assays-HaCaT cultures were serum-starved in the presence of AG 1478 (0.5 M; Alexis) as described previously (46). For mitogenic assays, cells were stimulated with increasing concentrations of FGF7 for 16 h. H]Thymidine (ICN) was added for 6 h, and thymidine incorporation was determined using a Wallac-1049 liquid scintillation counter (47).…”
Section: Methodsmentioning
confidence: 99%
“…Erk1/2 Activation and Mitogenic Assays-HaCaT cultures were serum-starved in the presence of AG 1478 (0.5 M; Alexis) as described previously (46). For mitogenic assays, cells were stimulated with increasing concentrations of FGF7 for 16 h. H]Thymidine (ICN) was added for 6 h, and thymidine incorporation was determined using a Wallac-1049 liquid scintillation counter (47).…”
Section: Methodsmentioning
confidence: 99%
“…2A). Further, we tested the effect of pCD and AP on proliferation of HaCaT keratinocytes in serum-free condition (Gamady et al, 2003;Grossman et al, 2004;Pozzi et al, 2004). The growth of cells in 10% FCS was taken as positive control and cell growth in medium without FCS served as a negative control.…”
Section: Pcd Acts As An Autocrine Mitogen On Keratinocytesmentioning
confidence: 99%
“…Growth factors, including epidermal growth factor (EGF) and keratinocyte growth factor, act in autocrine and paracrine manners to stimulate their cognate receptors, leading to activation of the various survival signaling pathways. [1][2][3][4][5][6] Opposed are signaling pathways leading to cell death such as c-Jun N-terminal kinase (JNK) and p38 MAPK. [7][8][9] We and others have shown that p38 MAPK and JNK are activated in keratinocytes by various stresses including UVB, oxidative stress, heat shock, proinflammatory cytokines and osmotic shock.…”
Section: Introductionmentioning
confidence: 99%